Use of Different Performance Measures by the Financial Market Participants - Наталья Евгениевна Шишкина; Владимир Владимирович Лапшин (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2015)
Natalia Evgenievna Shishkina - - National Research University "Higher School of Economics". Email: shishkina.n@gmail.comVladimir Vladimirovich Lapshin - - National Research University "Higher School of Economics". Email: lapshin.v@gmail.comThere are a huge number of measures for risk assessment, determination of performance but at times it is difficult enough to determine what or which of them can be more useful for a specific task. This requires understanding what interrelation there is between the measures, what common advantages and disadvantages they have, what strengths and weaknesseseach indicator of performance/risk has.In this article advantages, disadvantages,properties and area of application of 40 performance and risk measures are considered, the approach to the classification of measures is proposed, the scheme of interrelation between them is constructed (it is showed which of the measures are modification of other measures, which are particular case, which are used for calculation by other performance indicators). It is analyzed what negative consequences change of the measure, connected with using of asymmetry, kurtosis and/or moments of higher order, can have. It is investigated how modification/generalization of the measure influence its advantages and disadvantages.It is analyzed what new disadvantages, which are not present in main measure, its modification, aimed at getting rid of some disadvantages of parental measure, can cause.  It is considered what advantages, that special measures have, generalized their performance indicators, which have wider area of application, can lose. Approach to the use of these data by  different participants of the financial market (traders, investors and (or) managers) for making a decision quickly enough about what kind of measure or which set of measures should be used in order to solve the required task is proposed.